Rom, Italien: Architekturfragmente aus dem Steindepot der Diokletiansthermen - Beste, Heinz-Jürgen (e-Forschungsberichte des DAI, 2023)
The Thermae of Diocletian are Rome’s largest stone repository of ancient architectural sculptures. The museum management seeks to offer a wider range of exhibits and to establish a section on Roman architecture. The majority of the building elements from the repository shall be put on display in this new section. For this purpose, all relevant architectural fragments shall be catalogued and analysed, using digital photography, in order to attain an exact allocation to groups.